Invisible darkness : Jean Toomer & Nella Larsen - Larson, Charles R. (University of Iowa Press, 1993)
Invisible Darkness offers a striking interpretation of the tortured lives of the two major novelists of the Harlem Renaissance: Jean Toomer, author of Cane (1923), and Nella Larsen, author of Quicksand (1928) and Passing (1929). Charles R. Larson examines the common belief that both writers "disappeared" after the Harlem Renaissance and died in obscurity; he dispels the misconception that they vanished into the white world and lived unproductive and unrewarding lives. In clear, jargon-free language, Larson demonstrates the opposing views that both writers had about their work v